Comment on 'Attribute-Based Signatures for Supporting Anonymous Certification' by N. Kaaniche and M. Laurent (ESORICS 2016). (7th June 2017) - Vergnaud, Damien
Abstract: Anonymous credential systems enable users to authenticate themselves in a privacy-preserving manner. At the conference ESORICS 2016, Kaaniche and Laurent presented an anonymous certification scheme based on a new attribute based signature. In this note, we provide several attacks on their scheme.